Case Report: Unlocking arteria Lusoria challenges: sternotomy's role in a single-stage aneurysm repair and artery realignment - Ziyad Gunga; Lorène Rousseau; Margaux Wolff; Augustin Rigollot; Anna Nowacka; Filip Dulgorov; Zied Ltaief; Valentina Rancati; Rafael Trunfio; Sebastien Déglise; Matthias Kirsch (Frontiers in Cardiovascular Medicine)
Arteria lusoria (AL), an anomaly of the right subclavian artery, occurs in 2% of individuals and can cause symptoms such as dysphagia due to its retroesophageal course. Often associated with Kommerell's diverticulum (KD), a dilation at the artery's origin, this condition poses risks of rupture or dissection. Symptomatic cases and aneurysms necessitate surgical intervention, while asymptomatic cases may warrant observation. We present a case of a 44-year-old woman with dysphagia lusoria due to AL and KD, confirmed by imaging. Given anatomical complexities, a one-stage open surgical repair via sternotomy was performed. This involved resecting the KD and creating a neo-trajectory for the right subclavian artery using a Dacron tube graft. Cardiopulmonary bypass ensured safe manipulation, and post-operative imaging confirmed excellent outcomes, with complete symptom resolution. Surgical approaches for AL and KD vary depending on anatomy and symptomatology, ranging from open repairs to hybrid and endovascular techniques. Open thoracotomy remains the gold standard for young patients without comorbidities. Hybrid approaches are reserved for emergencies or high-risk patients, offering reduced morbidity but potentially higher complication rates. Advances in imaging and surgical techniques, including hybrid methods, have improved outcomes, with mortality rates significantly lower than historical benchmarks. The 2024 EACTS/STS guidelines recommend open surgery for young, fit patients (Class I, Level C) and hybrid approaches for emergencies or patients unfit for open surgery (Class I, Level C). Our case exemplifies the feasibility of sternotomy in providing precise, effective correction for KD with AL in a single operation while minimizing risks associated with other approaches.